COVID-19 and Breast Cancer in Brazil - Aline Ferreira Bandeira Melo Rocha; Ruffo Freitas-Junior; Glalber Luiz Rocha Ferreira; Danielle Cristina Netto Rodrigues; Rosemar Macedo Sousa Rahal (Frontiers Media S.A., 2023)
Objectives: This study aimed to evaluate COVID-19 effects on breast cancer screening and clinical stage at diagnosis in patients of 50-69 years of age receiving care within the public healthcare network (SUS) in 2013-2021 in Brazil and its macro-regions.Methods: This ecological study used Poisson regression to analyze trends in screening and staging. A secondary database was formed using SUS sources: outpatient data system of the SUS network and Oncology-Brazil Panel.Results: There was a reduction in screening, with an annual percent change of −5.9 (p < 0.022). The number of notified cases fell by 31.5% in 2020-2021 compared to 2018-2019. There was a 10.7% increase in the proportion of stage III/IV cases (p < 0.001) in 2020-2021 compared to 2013-2019, now surpassing the number of cases of early stage breast cancer.Conclusion: COVID-19 led to a reduction in breast cancer screening and an expressive increase in advanced tumors in users of the public healthcare network. Urgent interventions in public policies are required as the negative effects of the pandemic on the diagnosis/treatment of breast cancer are becoming apparent even earlier than expected.